Pemanfaatan Dana Desa untuk Infrastruktur Nagari, Dampaknya terhadap IDM dan Angka Kemiskinan di Sijunjung - Feri Yurnalis; Asdi Agustar; Osmet Osmet (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2025)
The study aims to analyze the utilization of Village Funds (DD) for nagari (village) infrastructure development and its impact on the Village Development Index (IDM) and poverty rates in Sijunjung Regency, West Sumatra. The research employed a mixed-methods approach using secondary data analysis for all 61 nagari and a qualitative multi-case study on selected nagari based on their IDM status. Secondary data collected covered DD allocation, types of infrastructure, IDM scores, and the number of poor residents from 2017 to 2019. The results indicate that DD allocation in Sijunjung was predominantly directed toward the Development Sector (averaging 89.58%), primarily for the construction of village roads. The analysis concludes that the DD allocation for infrastructure does not have a directly significant implication for increasing IDM or reducing the poverty rate in Sijunjung Regency. These findings suggest that the impact of infrastructure investment requires a longer time frame and is influenced by various factors beyond the DD policy for sustainable poverty alleviation